Copigmentation of Flavonoids of the Gadung Mango Bark (Mangifera Sp) as a Coloring Substance - Moh. Sahril; Vanny M. A. Tiwow; Afadil Afadil (Universitas Tadulako, 2021)
Flavonoids are pigments in the gadung mango bark that produce a yellow color. The research on copigmentation of flavonoids from gadung mango bark (Mangifera sp) as coloring agents was carried out by the maceration method using 96% ethanol. The extract obtained was concentrated using a vacuum rotary evaporator at 40 oC. The study aimed to determine levels of flavonoids and stability of color gadung mango bark on the inner and outer of the result copigmentation as a coloring agent. Measurement of total flavonoid levels at a wavelength of 520 nm and 700 nm using UV-Vis spectrophotometry. The results of this study indicate that the total flavonoids levels in the inner and outer gadung mango bark samples were 0.162 mg/g and 0.359 mg/g, respectively. The color stability of flavonoids of the gadung mango bark inside and outside as the results of copigmentation was stable at the temperature 35 oC and the results obtained in the color stability test of the hero cloth through washing soap water was with a 0 day in 5 hours.